2012
DOI: 10.1038/ijo.2012.139
|View full text |Cite
|
Sign up to set email alerts
|

A within-trial cost-effectiveness analysis of primary care referral to a commercial provider for weight loss treatment, relative to standard care—an international randomised controlled trial

Abstract: Background:Due to the high prevalence of overweight and obesity there is a need to identify cost-effective approaches for weight loss in primary care and community settings.Objective:We evaluated the cost effectiveness of two weight loss programmes of 1-year duration, either standard care (SC) as defined by national guidelines, or a commercial provider (Weight Watchers) (CP).Design:This analysis was based on a randomised controlled trial of 772 adults (87% female; age 47.4±12.9 years; body mass index 31.4±2.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,461 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…In the current environment, primary care professionals, especially GPs, are working at capacity as well as facing an increasing number of patients with obesity in need of treatment . GPs have little more than the standard 20‐minute consultation within which to try to improve the management of patients with obesity, a complex, multifactorial chronic condition . The capacity for GPs to refer to an established commercial weight‐loss program (such as WW) offering cost savings provides an additional feasible treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current environment, primary care professionals, especially GPs, are working at capacity as well as facing an increasing number of patients with obesity in need of treatment . GPs have little more than the standard 20‐minute consultation within which to try to improve the management of patients with obesity, a complex, multifactorial chronic condition . The capacity for GPs to refer to an established commercial weight‐loss program (such as WW) offering cost savings provides an additional feasible treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The WW cost used the market price of attending the program. For SC, the costs were for 10.7 GP consultations over the year, with a GP consultation lasting 20 minutes or less as per the Australian Medicare Benefits Schedule (item 23, http://www.mbsonline.gov.au). See Supporting Information Table S3 for a description of the intervention resources and unit costs.…”
Section: Methodsmentioning
confidence: 99%
“…We also showed that the CP was a cost‐effective treatment compared to SC, with both a within‐trial analysis and a modelled lifetime analysis . A sensitivity analysis was performed using the Australian medication costs per participant.…”
Section: Introductionmentioning
confidence: 91%
“…Based on the researchers' fi ndings, 2000-calorie diet would just cost $3.52 a day if it consisted of junk food, compared with $36.32 a day for a diet of low energy dense foods (PARKER-POPE, 2007). In the United Kingdom and in Germany, the cost of every lost kilogram from body weight was calculated as 122 USD (FULLER et al, 2013). Another US study examined the price elasticity of demand of sugarsweetened beverages, fast food restaurants, and fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%